Connective tissue disease-related interstitial lung disease is alleviated by tripterine through inhibition of the PI3K/Akt, apoptosis, and TNF-α signalling pathways - Zhu, Wen; Wang, Yifan; Liu, Chenxi; Wu, Yunxia; Li, Yehui; Wang, Yue (Frontiers in Pharmacology, 2022)
Background: Interstitial lung disease (ILD) is the major cause of morbidity and mortality in patients with various rheumatic diseases. However, more interventions need to be sought. Tripterine, an extract of Tripterygium wilfordii Hook. F, has been widely studied for its powerful anti-inflammatory effect. However, its mechanism of action in treating connective tissue disease-related (CTD)-ILD remains unclear. Purpose: To investigate the mechanism of tripterine in CTD-ILD treatment by combining network pharmacology and an in vivo experiment. Methods: The related targets of tripterine were obtained after searching the Traditional Chinese Medicine System Pharmacology Database and Analysis Platform, Comparative Toxicogenomics Database, GeneCards, Search Tool for Interacting Chemicals database, and SymMap database. Following this, Online Mendelian Inheritance in Man, GeneCards, Genebank, and DrugBank were used to screen the targets of CTD-ILD. A target-signalling pathway network was constructed using Cytoscape. Additionally, topological analysis was performed. Protein interaction analysis was performed using the STRING online analysis platform. Following this, Gene Ontology (GO) and the Kyoto Encyclopaedia of Genes and Genomes (KEGG) signalling pathway enrichment analyses were performed. Subsequently, the molecular docking between tripterine and the core targets was verified. Finally, experimental verification was performed in bleomycin-induced model mice. Results: A total of 134 common targets and 10 core targets of tripterine, including signal transducer and activator of transcription 3, tumour necrosis factor (TNF), v-rel avian reticuloendotheliosis viral oncogene homolog A, protein kinase B (Akt) α (Akt1), mitogen-activated protein kinase (MAPK) 1, Jun transcription factor family, tumour protein 53, MAPK3, nuclear factor kappa B subunit 1, and caspase 8, were obtained. GO enrichment analysis revealed that, while treating CTD-ILD, tripterine was mainly involved in cytokine receptor binding, receptor-ligand activity, signal receptor activation, cytokine activity, protein ubiquitination, deoxyribonucleic acid transcriptase activity, etc. The KEGG pathway enrichment analysis revealed that the most significant signalling pathways were multiple viral infections and the phosphatidylinositol-3-kinase (PI3K)/Akt, TNF, and apoptosis signalling pathways. Molecular docking results revealed that tripterine had good docking activity with the core targets. Experimental studies also demonstrated that tripterine could inhibit the activation of PI3K/Akt, apoptosis, and TNF-α signalling pathways in lung tissue and significantly improve lung pathology and collagen deposition in the model mice. Conclusions: This study preliminarily revealed the potential molecular biological mechanism of tripterine while treating CTD-ILD might be related to inhibiting the PI3K/Akt, apoptosis, and TNF-α signalling pathways. Tripterygium wilfordii Hook. F. and its extract could be used clinically for treating CTD-ILD.